2002
DOI: 10.1258/13576330260440664
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferenced continuing medical education in Nova Scotia

Abstract: Videoconferencing has been used for continuing medical education (CME) in Nova Scotia since a pilot project to four communities in 1995. The Nova Scotia Telehealth Network was developed after the pilot project. Using the network, the videoconferenced CME programme expanded over the next few years until in, 2000 1, 66 programmes were broadcast to 38 sites. During the expansion of the programme, we improved video quality and developed efficient methods of: scheduling and planning the content of the videoconferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…Negative aspects included: face-to-face consultations were already available or preferred, public spending on telemedicine had reduced funding for more basic health services, and telemedicine had been inadequately publicized. ............................................................................... In the present study, users of videoconferenced CME and teleconsultation valued these services as educational and clinically supportive, as has been found before [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . In addition, physicians practising in more rural communities (i.e.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Negative aspects included: face-to-face consultations were already available or preferred, public spending on telemedicine had reduced funding for more basic health services, and telemedicine had been inadequately publicized. ............................................................................... In the present study, users of videoconferenced CME and teleconsultation valued these services as educational and clinically supportive, as has been found before [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . In addition, physicians practising in more rural communities (i.e.…”
Section: Resultssupporting
confidence: 58%
“…Telemedicine can improve rural access to health-care and increase support for rural health practitioners [13][14][15][16] . It can also reduce the sense of isolation experienced by rural practitioners and their families, and improve morale 17 .…”
mentioning
confidence: 99%
“…9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Nelson R Mandela School of Medicine at the University of KwaZulu-Natal has increased the psychiatry registrar posts three-fold over the last three decades.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…Examples of educational activities in medical and nursing education using videoconferencing include undergraduate education (Callas et al 2004), resident education (O’Regan et al 2010), journal clubs (Ahn et al 2007), ward rounds (Allen et al 2002, 2007; Cunningham & Van der Merwe 2009; Gray et al 2009), continuing medical education (Allen et al 2002; Fitzgerald et al 2002; Karlinsky et al 2006), and clinical supervision (Xavier et al 2007).…”
Section: Introductionmentioning
confidence: 99%